Anorexia Nervosa Complicating Pediatric Crohn Disease—Case Report and Literature Review - Collins, Aedin; Nolan, Elizabeth; Hurley, Michelle; D'Alton, Antoinette; Hussey, Séamus (Frontiers in Pediatrics, 2018)
Crohn disease and anorexia nervosa share common symptoms of weight loss and reduced oral intake. The prevalence of both disorders has increased over time. Symptoms of Crohn disease and anorexia nervosa can mimic each other leading to a delayed diagnosis and requiring complex, multidisciplinary management. Here we present a case of a fifteen year old girl with Crohn disease who subsequently developed anorexia nervosa, and review the published literature on the occurrence of both diagnoses.